Influencing factors of farmers' cognition on agricultural mulch film pollution in rural China - Xue, Yinghao; Guo, Jianbing; Li, Chang; Xu, Xiangbo; Sun, Zhanxiang; Xu, Zhiyu; Feng, Liangshan; Zhang, Linxiu (The Science of the total environment, 2021)
The extensive use and inadequate recycling of agricultural mulch film has caused serious environmental pollution. Studies have shown that farmers' cognition on agricultural mulch film pollution can affect mulch film recycling, but studies about farmers' cognition on agricultural mulch film pollution is less. The sample is 2025 households in 5 provinces of China in 2018, the study is based on the theory of planned behavior, and the ordered logit model is used to analyze farmers' cognition on agricultural mulch film pollution. As shown in the results: (1) only 53.78% of farmers think that the agricultural mulch film can pollute farmland; (2) the attitude of farmers who are willing to strengthen the knowledge of environmental protection and spend money to protect the environment are positively correlated with cognition; (3) from the subjective norm, farmers who are subject to environmental government regulations and village regulations have higher cognition, but the informal institution is more effective; (4) from the perceived behavioral control, when farmers are dissatisfied with the surrounding environment, they are more likely to have higher cognition; and (5) from the household characteristics, the proportion of non-agricultural income and age of household head are negatively correlated with cognition, and farmers with higher education level have higher cognition. As for the suggestions on improving the cognition of smallholder farmers, special attention should be paid to strengthening the restraint effect of village regulations on small size, large amount and scattered smallholder farmers, rather than relying on the formal institution blindly. [Display omitted] •Mismanagement of mulch film is causing environmental problems in rural China.•National representative micro-level data was used to explore influencing factors of cognition.•Half of farmers think that the agricultural mulch film can pollute farmland.•The attitude, subjective norm, perceived behavioral control and household characteristics affect cognition.•Pay attention to village regulations, not just formal institution.